BRIDGING THE GAP: CPEC ON REGIONAL CONNECTIVITY STRENGTHENING BONDS IN CENTRAL ASIA AND THE MIDDLE EAST - Adiba Tahir Gill; Ubaid Azhar Zaman; Muhammad Ismail (PalArch's Journal of Archaeology of Egypt / Egyptology, 2023)
The China-Pakistan Economic Corridor (CPEC) has emerged as a significant initiative aimed at strengthening regional connectivity and fostering bonds between Central Asia, the Middle East, and beyond. CPEC is a flagship project of China's Belt and Road Initiative (BRI) and encompasses a vast network of infrastructure development projects, including transportation networks, energy pipelines, and industrial zones. This abstract explores the role of CPEC in bridging the gap between countries in Central Asia and the Middle East, and its potential to enhance regional cooperation and economic integration. CPEC's strategic location, connecting the Arabian Sea to China's northwestern region via Pakistan, has the potential to significantly reduce transportation costs and time for trade between the participating countries. This infrastructure connectivity is expected to boost economic activities, attract foreign investment, and facilitate the movement of goods, services, and people across the region.The corridor aims to establish energy pipelines and projects to alleviate energy shortages, promote renewable energy sources, and enhance energy security in the region. This energy cooperation is crucial for sustaining economic growth and development, as well as addressing the energy demands of participating nations. CPEC has the potential to facilitate cultural and people-to-people exchanges between Central Asia, the Middle East, and China. Increased connectivity and improved transportation networks can lead to enhanced tourism, educational exchanges, and cultural understanding, fostering closer ties among the nations involved. CPEC has the potential to serve as a catalyst for regional connectivity, economic growth, and closer ties between Central Asia, the Middle East, and China. By addressing the challenges and leveraging the opportunities presented by CPEC, participating countries can strengthen bonds, promote peace and stability, and unlock the full potential of the region's resources and human capital.